Synthesis, biological evaluation and in silico studies of 2-aminoquinolines and 1-aminoisoquinolines as antimicrobial agents. (February 2023) - Vashistha, Aditi; Kumar, Sunil; Kirar, Seema; Sharma, Nikhil; Das, Bhanuranjan; Banerjee, Uttam Chand; Pawar, Sandip V.; Kumar, Rajnish; Yadav, Ashok Kumar
Abstract: The current study reports synthesis of 2-aminoquinolines and 1-aminoisoquinolines derivatives and their characterization. Further, in vitro studies were conducted to determine antimicrobial activities. Compound 3 h showed maximum activity against B. subtilis (IC50 : 0.10±0.02 µM) and E. coli (IC50 : 0.13±0.01 µM) whereas compound 3i showed higher antimicrobial activity against E. coli (IC50 : 0.11±0.01) and C. viswanathii (IC50 : 0.10±0.05 µM). Safety profiles of the most potent derivatives were evaluated utilizing cell viability assay using RAW 264.7 and HeLa cell lines and in vitro hemolytic assay was carried out freshly isolated RBC from healthy rat. Furthermore, in silico studies, like molecular docking, binding free energy calculations and ADME predictions were done to get the best lead candidates. Additionally, molecular dynamic simulation for 100 ns was performed to know stability of protein and ligand complex. The active compounds were found to be non-toxic and non-hemolytic and hold great promise to become newer antimicrobial agents. Graphical Abstract: ga1 HighLights: 2-Aminoquinolines and 1-aminoisoquinolines derivatives were synthesized. In vitro studies of the synthesized compounds were conducted to determine antimicrobial activities. Safety profiles of the most potent derivatives were evaluated utilizing cell viability assay using RAW 264.7 and HeLa cell lines. Molecular docking, binding free energy calculations and ADME predictions were carried out to know the best lead candidates. Molecular dynamic simulation was performed to see stability of protein and ligand complex.